2020
DOI: 10.1080/23802359.2017.1422413
|View full text |Cite
|
Sign up to set email alerts
|

Complete sequence of mitochondrial DNA of Gracilaria edulis (Rhodophyta)

Abstract: Herein, the complete Gracilaria edulis mitogenome was determined and analysed. The complete G. edulis mitogenome length was 25,708 bp. The mitogenome contains 50 genes, including 24 proteincoding, two rRNA, and 23 tRNA genes and one unidentified open reading frame (ORF). Of the 24 protein-coding genes, 23 (95.83%) ended with the TAA stop codon, and one (4.17%) with TAG (rpl20). All protein-coding genes in G. edulis were concluded to use the start codon ATG. Mitogenome phylogenetic analysis revealed that G. edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Alternatively, the SNVs and ambiguities observed could be due to each dataset having been sequenced from DNA originating from multiple specimens. While mtDNA is typically sequenced from an individual specimen (see, for example, Lee et al, 2006;Zhao et al, 2011;Sedanza et al, 2020), the general procedure for the extraction of baculovirus occlusion bodies (OBs) is from multiple infected insects pooled together to increase the resulting yield. With the NGS data utilized in this study originally generated to determine the genome sequence of the baculovirus CrleGV, DNA was extracted from multiple T. leucotreta larvae, and therefore contains mtDNA from multiple specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the SNVs and ambiguities observed could be due to each dataset having been sequenced from DNA originating from multiple specimens. While mtDNA is typically sequenced from an individual specimen (see, for example, Lee et al, 2006;Zhao et al, 2011;Sedanza et al, 2020), the general procedure for the extraction of baculovirus occlusion bodies (OBs) is from multiple infected insects pooled together to increase the resulting yield. With the NGS data utilized in this study originally generated to determine the genome sequence of the baculovirus CrleGV, DNA was extracted from multiple T. leucotreta larvae, and therefore contains mtDNA from multiple specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Mitogenomes sequence is one of the fundamental approaches used to analyze the taxonomy and phylogeny of red algae (Boo et al 2016). Sedanza et al (2020) determined that the complete G. edulis mitogenome length was 25,708 bp and this species clustered together with G. changii and G. salicornia. Wang et al (2020) found G. chilensis plastid genome sequence was 185,640 bp and it had a closer relationship with Gracilaria tenuistipitata var.…”
Section: Molecular Identificationmentioning
confidence: 99%
“…Therefore, it is necessary because of being capable to provide more accurate information on a species genetic diversity. Some molecular studies of Gracilariaceae have been conducted (Liu et al 2017;Sedanza et al 2020;Wang et al 2020), but not in Indonesia. A molecular study of this country's Gracilaria species was conducted using RAPD marker (Windarsih et al 2019) to characterize their genetic profile with random single oligonucleotides, however, the RAPD also has limitations due to its low reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…Chloroplast genome of U. prolifera was taken as seed sequences for sequence splicing about the complete chloroplast genome of U. torta using NOVOPlasty software (Sedanza et al. 2020 ). The extended chloroplast genome contigs was obtained, and then the extended contigs were compared with the chloroplast genome sequence of U. prolifera to obtain the correct contig sequence.…”
mentioning
confidence: 99%